Field Bio-efficacy and Residue Dynamics of the Fungicide Polyoxin D Zinc Salt 5% SC in Grape (Vitis vinifera) - Deore, Pushpa; Hingmire, Sandip; Shinde, Dattatray; Pudale, Anjali; T. P, Ahammed Shabeer; Banerjee, Kaushik; Thosar, Ratna; Saha, Sujoy (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were carried out to evaluate the bio-efficacy and residue dynamics of Polyoxin D Zinc salt 5% SC in grape during 2014-2015 and 2015-2016 at ICAR-National Research Centre for Grapes, Pune. Polyoxin D Zinc salt 5% SC @ 600 ml ha-1 gave the best control of the disease, both in the leaves and bunches with a percent disease control of 56.4 and 75.7 respectively, as compared to untreated control. The percent disease control of the test fungicide Polyoxin D Zinc salt 5% SC @ 600 ml ha-1 was superior to all the triazoles viz. Flusilazole 40 EC, Hexaconazole 5 EC and Myclobutanil 10 WP, used in the study. The yield data reflected a similar trend wherein the maximum percent increase in yield was observed in case of Polyoxin D Zinc salt 5% SC @ 600 ml ha-1 i.e. 57.47 as compared to untreated control. However, all the triazoles manifested a higher percent increase in yield as compared to the lowest dose of the test fungicide i.e. 200 ml ha-1. For the detection and quantification of polyoxin D residue in grape, we have developed an efficient and effective analytical method, using liquid chromatography-tandem mass spectrometry (LC-MS/MS), in field treated samples. The residue data had excellent fit to 1st+1st order models giving r2 value of >0.99 with a half-life (t1/2) 8.0 days for recommended dose and 14.5 days for double dose. These findings are useful for effective disease management in grape crop amalgamated with food safety and consumer satisfaction.